2022
DOI: 10.3390/buildings13010009
|View full text |Cite
|
Sign up to set email alerts
|

Green Home Buying Intention of Malaysian Millennials: An Extension of Theory of Planned Behaviour

Abstract: The empirical study aimed to examine the factors affecting green home buying intention in Malaysia. The study adopted the popular theory of individual decision-making, the theory of planned behaviour, but extended it with a few new variables to get better predictability. Based on the cross-sectional survey method and quota sampling technique, the instrument-like questionnaire was distributed to the potential buyers who had the intention to buy a home. Data were collected from 741 potential buyers who are young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 111 publications
0
0
0
Order By: Relevance
“…The items related to GBPE, GBEE, GBFC, GBSI, GBHM, and GBIC were adapted from different studies (i.e., Huang, 2023; Shahzad et al, 2022; Shi et al, 2022; Widyanto et al, 2022). The measure of environmental concern was adapted from Masukujjaman et al (2022). All items were developed using a five‐point Likert scale, anchored by “strongly disagree (1)” and “strongly agree (5)”.…”
Section: Methodsmentioning
confidence: 99%
“…The items related to GBPE, GBEE, GBFC, GBSI, GBHM, and GBIC were adapted from different studies (i.e., Huang, 2023; Shahzad et al, 2022; Shi et al, 2022; Widyanto et al, 2022). The measure of environmental concern was adapted from Masukujjaman et al (2022). All items were developed using a five‐point Likert scale, anchored by “strongly disagree (1)” and “strongly agree (5)”.…”
Section: Methodsmentioning
confidence: 99%
“…It means individuals with a strong ethical selfidentity have a heightened awareness of their personal values related to environmental sustainability, social responsibility, and ethical consumption. This ethical self-identity influences their perceptions and decisions regarding what they consider as morally acceptable or aligned with their ethical beliefs (Masukujjaman et al, 2023;Tarinc et al, 2023b).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…They argue that attitudes, perceived behavioral control, and subjective norms cannot fully cover and explain the intentions and behaviors of people in all domains. Apart from these three variables, many behaviors are also affected by other factors [47,52,53]. For instance, in the field involving past experience, the past behavior should be added as an important variable, while in the field related to integrity, moral hazard or moral concept is an important factor.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Throughout the last few decades, researchers have sought to improve the application degree and explanatory abilities of the TPB model through changing approaches and/or adding new variables [51,53,64]. Ajzen [26] showed that two points should be noted in the extension of the theory of planned behavior: (1) the newly added variables should be clearly defined and distinguished from the original variables, and (2) the newly added variables should be matched with the original variables.…”
Section: Extended Planned Behavior Theory Variable-past Experiencementioning
confidence: 99%